Analysis of the Influence of Competency, Work Motivation, and Work Environment on Employee Performance of PT Graha Sakura Jaya (Grand Sakura Hotel) Medan - Darni Br Barus; Kholilul Kholik (Universitas Muhammadiyah Palu, 2024)
This study aims to analyze the influence of competence, work motivation, and work environment on employee performance at PT Graha Sakura Jaya (Hotel Grand Sakura) Medan. This research method is quantitative with an associative approach. Data collection was carried out by distributing questionnaires. The research data was processed with SPSS 25. The results showed that Competence, Work Motivation and work environment have a positive and significant effect on employee performance at PT Graha Sakura Jaya (Hotel Grand Sakura) Medan both partially and simultaneously. Competence has a positive and significant effect partially on employee performance at PT Graha Sakura Jaya, where the t count value is 3.245 and t table 1.99547 or t count> t table = 3.245> 1.99547 with a significant value of 0.031 which means the significant value is greater than 0.05 (0.031 <0.05). So H1 is accepted. Work Motivation partially has a positive and significant effect on Employee Performance of PT Graha Sakura Jaya where the t count value is 3.101 and t table 1.99547 or t count> t table = 3.101> 1.99547 with a significant value of 0.049 which means the significant value is greater than 0.05 (0.049 <0.05). So H2 is accepted. The work environment partially has a positive and significant effect on Employee Performance of PT Graha Sakura Jaya where the t count value is 3.524 and t table 1.99547 or t count> t table = 3.524> 1.99547 with a significant value of 0.005 which means the significant value is greater than 0.05 (0.001 <0.05). So H3 is accepted. Competence, work motivation and work environment together (simultaneously) have a positive and significant influence on employee performance at PT Graha Sakura Jaya (Hotel Grand Sakura Jaya) Medan where the calculated f value is 5.507 and f table 2.740 or calculated f> f table = 5.507> 2.740 with a significant value of 0.002 which means the significant value is smaller than 0.05 (0.002 <0.05). So H4 is accepted. It can be concluded that the hypotheses H1, H2, H3, and H4 are proven true and can be accepted because the results of the study are in line with the proposed hypothesis.